Law Enforcement Against Handling Traffic Accidents Through Non Line Under Penal of Legal Culture of Indonesian Police in Kudus - Ngatmin Ngatmin; Umar Ma’ruf (Jurnal Daulat Hukum, 2018)
The Police of the Republic of Indonesia (POLRI) is a tool that contributes to maintaining state security and public order. The purpose of this research: knowing and analyzing the traffic accident set in the current positive criminal law further handling traffic accidents and then through non penal later barriers and settlement solutions handling traffic accidents then then through non penal.This research is legal using empirical juridical approach or commonly referred to as the Juridical Sociological. According to his level, the study was specified as descriptive analytical research.The results of this study are (1) In the conduct of law enforcement against traffic criminal offenses remain consistent with the provisions of the Criminal Code and Act No. 22 Of 2009 regarding Traffic and Road Transportation. (2) Allowing involved to make peace (3) Barriers handling track non penal offenders and victims and their families do not support the settlement outside the court, the solutions do is keep highlighting persuasive conclusion in this research that law enforcement against criminal acts and cross remains consistent with the provisions of the Criminal Procedure Code and Act No. 22 of 2009 on Traffic and Transportation, opportunity for the parties involved to make peace. Perpetrators and victims of personal character that does not support the settlement outside the court.Keywords: Law Enforcement; Traffic Accident; Non Line Penal Of Legal Culture.